Rethinking Resident Supervision to Improve Safety: From Hierarchical to Interprofessional Models - Tamuz, Michal (2011)
BACKGROUND: Inadequate supervision is a significant contributing factor to medical errors involving trainees but supervision in high-risk settings such as the Intensive Care Unit (ICU) is not well studied. OBJECTIVE: We explored how residents in the ICU experienced supervision related to medication safety not only from supervising physicians but also from other professionals. DESIGN, SETTING, MEASUREMENTS: Using qualitative methods, we examined in-depth interviews with 17 residents working in ICUs of three tertiary-care hospitals. We analyzed residents' perspectives on receiving and initiating supervision from physicians within the traditional medical hierarchy and from other professionals, including nurses, staff pharmacists and clinical pharmacists (“interprofessional supervision”). RESULTS: While initiating their own supervision within the traditional hierarchy, residents believed in seeking assistance from fellows and attendings and articulated rules of thumb for doing so; however, they also experienced difficulties. Some residents were concerned that their questions would reflect poorly on them; others were embarrassed by their mistaken decisions. Conversely, residents described receiving interprofessional supervision from nurses and pharmacists, who proactively monitored, intervened in, and guided residents' decisions. Residents relied on nurses and pharmacists for non-judgmental answers to their queries, especially after-hours. To enhance both types of supervision, residents emphasized the importance of improving interpersonal communication skills. CONCLUSIONS: Residents depended on interprofessional supervision when making decisions regarding medications in the ICU. Improving interprofessional supervision, which thus far has been under-recognized and underemphasized in graduate medical education, can potentially improve medication safety in high-risk settings.